Estudio de factibilidad para la creación de una empresa comercializadora de plantas ornamentales en el cantón Lago Agrio, provincia de Sucumbíos. - Ríos Merchán, Verónica Carolina (2014)
Ecuador is a country with a privileged geographic location that provides great benefits in terms of biodiversity, agricultural competitiveness determinant factor, and also has different types of climates a few distances. Therefore it is a predominantly agricultural country known for the excellence of its flowers. In addition to the flower where activity and production of ornamental plants has developed an advanced knowledge and technology where high quality standards involved in this type of activity. Taking as a basis the above, we can say that the production of ornamental plants is a new and promising activity in the economic field that requires the full attention and study, in order to develop new economic activities to boost the economy and trade nationwide. So let us describe some generalities that arose in the development of this project. In this research work the different methods and techniques as applied : Deductive - Inductive Method, which was used to compare with the surrounding reality with the results that materialized through the conclusions that emerged from this research, this in turn served to meet the actual requirement of ornamental plants throughout the province of Sucumbíos , the Analytical Method possible to analyze each of the internal components , external causes and the relationship between them , which facilitated the analysis of information and data obtained , this method also allowed us to know the advantages and disadvantages of carrying out this project, the statistical Method - Mathematician, facilitated the interpretation and understanding of statistics as: implementation and tabulation of the respective survey , projections, financial indicators (IRR, VAN, PRC ), and thus allow us to know the reality about the company over the 10 year life of it. Regarding the Market Study and according to surveys, it may indicate that the results were summarized by Tab and then perform market analysis, determining a potential demand 104,500, a Royal Request 41,800 and Effective Demand of 23,408 families and 795,872 have as demand Expected ornamentals; Similarly Unmet demand is 701912 ornamental plants, this also allowed us to determine that the project can and should be performed by the results obtained in the analysis of demand, supply and levels of marketing this product. You can indicate that unmet demand reflects the potential of ornamental plants in the province of Sucumbíos market we can also indicate that the installed capacity of the project determines that the company will be able to produce 26400 ornamental plants, whereas capacity utilization begins with the 80 % begin with the production of ornamental plants 21120 in the first year. Also determined that the most appropriate location of the company is the Location B. Streets and Rio Aguarico Ecuador. The production process requires the use of suitable equipment, which will be guaranteed to get a quality product at reasonable prices. Subsequently determining project engineering process diagrams, characteristics of operation and management, technical requirements as equipment, facilities develops. Similarly an administrative study determined as a Limited Liability Company , and functional organizational structure to the hierarchical levels both Legislative, Executive , Consultant Level, was carried Support Assistant , Operational Level , as well as operating manuals , charts , which served as a good guide for implementing organization, as it will have the following staff : Manager , a Secretary a Concierge - Guardian, one Accountant who will be part of the administrative staff. Financially we can indicate that the project reaches an investment of $ 67,838.71. The financial evaluation shows the following results: According to the NPV of this project gives a positive value of $ 92,035.46, indicating that the project or investment is suitable. For this project, the IRR is 38.48 %, with the satisfactory value for the project, also determined that the time required to recover the original investment is 3 years, 7 months and 20 days, for this project, the sensitivity values are less than one, therefore not affecting the project an increase of 22.55% in costs and a decrease of 16.13% in revenues, i.e. the project is not sensitive to these changes. Among the most significant findings and recommendations have which market research developed in the province of Sucumbíos, we determined that the project can and should be performed by the results obtained in the analysis of supply and demand. It has been demonstrated that there is considerable unmet need in the region ornamentals.